Synthesis of highly stable κ/ι-hybrid carrageenan micro- and nanogels via a sonication-assisted microemulsion route - Rodriguez, S.; Torres, F.G.; Arroyo, J.; Gonzales, K.N.; Troncoso, O.P.; López, D. (SAGE Publications, 2020)
Novel carrageenan micro- and nanogels were developed via a sonication-assisted microemulsion processing route. The diameter of the dry samples ranged 197.3 −421.35 nm whereas the diameter of the samples suspended in water ranged 467.8–605.9 nm. Hybrid κ/ι-carrageenan, rather than κ- or ι-carrageenan was used for the first time for the preparation of micro- and nanogels. KCl was used as a cross-linking agent and Tween 80 was used as surfactant. The micro- and nanogels suspended in water were found to simultaneously exhibit a lower diameter, and a lower swelling ratio with higher Tween 80 content. The micro- and nanogel suspension yields a zeta potential value of −50.5 mV, superior to values reported elsewhere for pure κ- or ι-carrageenan micro- and nanogels. The high stability was attributed to the high hydrophile-lipophile balance (HLB = 15) value of Tween 80. These results suggest that hybrid κ/ι-carrageenan micro- and nanogels are promising candidates for smart therapeutics applications.
Keywords: Nanogel; Sonication; Microemulsion; Carrageenan; Swelling; Zeta potential; Chemical engineering; Materials science; Pulmonary surfactant; Suspension (topology); Chromatography; Chemistry; Nanotechnology; Nanoparticle; Composite material; Drug delivery; https://purl.org/pe-repo/ocde/ford#2.10.01